Utilizing Cartoon Movie Media to Improve Listening Skill of IV Graders Elementary School SDN Prambontergayang 2 - Aditya, Jepri Perdana (JPP (Jurnal Pendidikan dan Pembelajaran), 2018)
This research intends to examine the listening skill of IV Graders of elementary school at SDK Wololanu after learning with cartoon film media. This research was a classroom action research (commonly referred to as CAR). It employed Kemmis and Taggart research model and used qualitative approach. The data were obtained by using test, observation, field notes, and documentation. The results show that cartoon film media improves listening skills of students.Tujuan penelitian ini adalah untuk mengetahui kemampuan menyimak siswa kelas IV SDK Wololanu setelah diterapkan media film kartun. Penelitian ini merupakan jenis Penelitian Tindakan Kelas (PTK) model Kemmis dan Taggart dan menggunakan pendekatan kualitatif. Data dikumpulkan dengan teknik tes, observasi, catatan lapangan dan dokumentasi. Hasil penelitian ini menunjukkan media film kartun dapat meningkatkan kemampuan menyimak siswa.